Monetary policy communication and inflation expectations: New evidence about tone and readability - Gianni Carotta; Miguel Mello Costa; Jorge Ponce (Latin American Journal of Central Banking (LAJCB), 2023)
We contribute new empirical evidence on monetary policy communication and inflation expectations by firms. First, we construct a new indicator of the perceived tone of monetary policy communication that complements traditional indicators of the effective tone. Both have the expected negative sign and are statistically significant in panel data regressions with firms' inflation expectations as the dependent variable, suggesting that communication has an important effect over inflation expectations. We also compute readability and perspicuity indicators of the communications. Better readability of monetary policy communication reinforces the effect of the tone. Impact is larger when combined with the indicator of effective tone, suggesting that readability is an important component in monetary policy communication.
Keywords: C23; E52; E58; 330; Inflation expectations; Monetary policy communication; Readability; Tone